The economic competitiveness of renewable energy : pathways to 100% global coverage - Hoffmann, Winfried (Physicist) (Hoboken, New Jersey : Scrivener Publishing/Wiley., 2014)
"Argues that 100% coverage of the global energy needs by renewable technology is much more probable than previously thought; explains how energy efficiency technologies will be able to drastically reduce the energy consumption for the same quality of life; demonstrates that traditional energy technologies are not able to sustainably support the future energy requirements of a growing world population; and discusses the most relevant renewable energy technologies, including solar photovoltaic, solar thermal and wind"--
Analysis of Today's Energy Situation -- The Importance of Energy Efficiency Measures -- Overview of the Most Important Renewable Energy Technologies -- PV Market Development -- PV Value Chain and Technology -- The Astonishing Predictive Power of Price Experience Curves -- Future Technology Development -- Future Energy Projections : the 150 Peta-Watt-Hour Challenge -- Likelihood of and Timeline for a World Powered by 100% Renewable Energy -- Conclusion: The 100% Renewable Energy Puzzle.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Renewable energy sources; Renewable energy sources -- Economic aspects; Energy industries; Energy policy; TECHNOLOGY & ENGINEERING / Power Resources / General; Industries -- Energy conservation; Industries -- Energy consumption; Energy industries; Energy policy; Renewable energy sources; Renewable energy sources -- Economic aspects; Renewable energy sources; Renewable energy sources / Economic aspects; Energy industries; Energy policy; Electronic books; Electronic books; Electronic books